The association between non- and pro-healthy diet indices and the risk of colorectal cancer: a case-control study - Maryam Ranjbar Zahedani; Iman Kazemi; Ali Kohanmoo; Zainab Shateri; Mohammad Mahdi Rajabpour; Mehran Nouri; Bahram Rashidkhani (BMC Gastroenterology)
Abstract Background The Non-Healthy Diet Index (NHDI) and the Pro-Healthy Diet Index (PHDI) are two novel indices that evaluate the healthiness of a diet based on the consumption of several food groups. This study aimed to evaluate the association between adherence to the PHDI and NHDI and colorectal cancer (CRC) risk in the Iranian population. Methods The current study was conducted as a hospital-based research using a case (n = 71)- matched-controls (n = 142) design in Tehran, Iran. A semi-quantitative food frequency questionnaire was utilized to determine participants’ dietary intake after confirming the diagnosis of CRC and at the time of the interview. The PHDI-10 was employed to assess the consumption of foods with positive health effects, which is linked to the frequency of consuming 10 food groups, and the NHDI-14 was used to assess the consumption of foods that have detrimental effects on health, based on the frequency of 14 food groups. Logistic regression was used to evaluate the association between continuous PHDI and NHDI scores and their tertiles with CRC. Results The results indicated that individuals in the highest tertile of the PHDI showed a lower CRC risk compared to those in the lowest tertile (adjusted model- odds ratio (OR) = 0.25; 95% confidence interval (CI): 0.10–0.61; P = 0.002). Also, lower odds of CRC risk were seen with each unit change in the total score of PHDI in the adjusted model (OR = 0.86; 95% CI: 0.76–0.96; P = 0.009). In contrast, individuals in the highest tertile of the NHDI showed a higher risk of CRC compared to those in the lowest tertile (OR = 2.62; 95% CI: 1.09–6.27; P = 0.030) in the adjusted model. Also, higher odds of CRC risk were observed with each unit increase in the total score of NHDI in the adjusted model (OR = 1.13; 95% CI: 1.03–1.25; P = 0.008). Conclusions The present study showed that higher adherence to PHDI and NHDI is associated with lower and higher CRC risk, respectively. These results provide valuable insights into the roles of healthy and unhealthy diets in CRC prevention.